A method for preparing bacteriostatic octanoylhydroxamic acid

By using an aqueous ethanol solution and a specific catalyst in the preparation of octanoyl hydroxamic acid, the problems of cumbersome operation, high energy consumption and low product purity in the prior art are solved, and an efficient and environmentally friendly preparation method is achieved, which is suitable for industrial production.

CN116715605BActive Publication Date: 2025-04-25HEZE NEW ORIENTAL DAILY CHEM TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310603040.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-26
Publication Date
2025-04-25
Estimated Expiration
2043-05-26

AI Technical Summary

Technical Problem

The existing preparation methods for octanyl hydroxamic acid are complicated to operate, have high production energy consumption, high environmental pressure, low raw material conversion rate, and low product yield and purity.

Method used

Using aqueous ethanol solution as solvent medium, hydroxylamine and methyloctanoate as reaction raw materials, the process parameters are optimized to achieve a green and safe catalytic reaction by loading the catalysts of lanthanum oxide and tetramethylammonium hydroxide.

Benefits of technology

It simplifies the preparation process, reduces production costs, improves raw material conversion rate, product yield and purity, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure GDA0005288105850000071
    Figure GDA0005288105850000071
  • Figure GDA0005288105850000081
    Figure GDA0005288105850000081
  • Figure GDA0005288105850000082
    Figure GDA0005288105850000082
Patent Text Reader

Abstract

The present application relates to the technical field of chemical synthesis, and specifically discloses a method for preparing antibacterial octanoyl hydroxamic acid. The method comprises the following steps: adding a catalyst to an ethanol aqueous solution, stirring and dispersing the mixture, adding hydroxylamine and methyl octanoate, stirring the mixture until the reaction is completed, adjusting the pH value, filtering and recovering the precipitate, evaporating the filtrate, and recrystallizing the filtrate to obtain octanoyl hydroxamic acid. The catalyst comprises a catalytic carrier and an active component. The active component comprises lanthanum oxide and tetramethylammonium hydroxide. The method uses an ethanol aqueous solution as a solvent medium, hydroxylamine and methyl octanoate as reaction raw materials, and a catalytic carrier loaded with lanthanum oxide and tetramethylammonium hydroxide as a catalyst. By optimizing process parameters, octanoyl hydroxamic acid is prepared using a green and safe catalyst. The method of the present application has the advantages of simple operation, mild reaction conditions, high raw material conversion rate, high product yield and high purity, and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of chemical synthesis, and more specifically, to a method for preparing bacteriostatic octanoylhydroxamic acid. Background Art

[0002] Caprylhydroxamic acid (CHA for short) is an organic acid that can maintain a non-ionized state throughout the acidic to neutral range. It has a highly efficient chelating effect, can inhibit the active elements required by mold, and restrict the environment required for microbial growth. It is an ideal antibacterial agent and is widely used in the fields of cosmetics, medicine and fine chemicals. In recent years, it has been used more and more widely in cosmetics. In addition to being used as a chelating agent in cosmetics, it is also used as a tyrosinase inhibitor in whitening products, and even as a preservative synergist in cosmetics.

[0003] In the related art, there are many disclosed methods for preparing CHA, among which the commonly used preparation method is: under the action of base catalysis, hydroxylamine hydrochloride or hydroxylamine sulfate is used as the main raw material, and an oximation reaction is carried out with a caprylic acid ester compound to produce caprylhydroxamate, and then the main product caprylhydroxamic acid is obtained after acidification. The above preparation method has the problems of cumbersome operation, first cooling, then heating, and then cooling in the preparation process, high energy consumption in production, and salt-containing wastewater will be generated in the production process, which has great environmental pressure and is not conducive to industrial production; and because the reaction raw materials and caprylhydroxamic acid have poor stability and easy decomposition under alkaline conditions, the raw material conversion rate is low, and the yield and purity of the caprylhydroxamic acid product finally obtained are low. Based on the above statement, it is of positive significance to develop a preparation method that is simple to operate, has simple reaction conditions, is green and environmentally friendly, and can improve the stability of raw materials and products, thereby improving the yield and purity of products, and obtaining a method for antibacterial caprylhydroxamic acid. Summary of the invention

[0004] In order to solve the problems of the current preparation method of octanoylhydroxamic acid, such as complicated operation, high energy consumption in production, great environmental pressure, low raw material conversion rate, low product yield and purity, etc., the present application provides an antibacterial preparation method of octanoylhydroxamic acid.

[0005] The present application provides a method for preparing antibacterial octanoylhydroxamic acid, which adopts the following technical scheme:

[0006] A method for preparing bacteriostatic octanoylhydroxamic acid comprises the following preparation steps:

[0007] After adding a catalyst to an ethanol aqueous solution and stirring to disperse, hydroxylamine and methyl octanoate are added and stirred until the reaction is completed, the pH value is adjusted and the precipitate is recovered by filtration, and the filtrate is evaporated to dryness and then recrystallized to obtain octanoylhydroxamic acid;

[0008] The catalyst comprises a catalytic carrier and an active component; the active component comprises lanthanum oxide and tetramethylammonium hydroxide.

[0009] Preferably, the ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 85-95%.

[0010] Preferably, the mass ratio of hydroxylamine to methyl octanoate is 1:4.8-5.2.

[0011] Preferably, the mass ratio of the catalyst to hydroxylamine is 1-1.2:10.

[0012] By adopting the above technical scheme, the present application uses ethanol aqueous solution as a solvent medium, hydroxylamine and methyl octanoate as reaction raw materials, and a catalytic carrier loaded with lanthanum oxide and tetramethylammonium hydroxide as a catalyst. By optimizing the process parameters, a green and safe catalyst is used to catalyze the preparation of octanoylhydroxamic acid. The preparation method of the present application is simple to operate, mild reaction conditions, high raw material conversion rate, high product yield and high purity, and is suitable for industrial production.

[0013] Preferably, the catalyst carrier is prepared by the following method:

[0014] Add water to sodium pyrophosphate and sodium tripolyphosphate and stir to dissolve to obtain a mixed solution;

[0015] Zeolite and silicon dioxide are added to the mixed solution and stirred and mixed, then a silane coupling agent is added and mixed continuously, and the mixture is dried and ground to obtain the desired catalytic carrier.

[0016] Preferably, the mass ratio of the sodium pyrophosphate, sodium tripolyphosphate and water is 3:1:10.

[0017] Preferably, the mass ratio of the mixed solution, zeolite, silica and silane coupling agent is 10:4:1:0.2.

[0018] By adopting the above technical scheme, the present application uses a composite of zeolite and silica as a carrier component, adds the carrier component to a mixed aqueous solution of sodium pyrophosphate and sodium tripolyphosphate for modification, and then adds a silane coupling agent for further modification. The resulting catalytic carrier has good dispersion performance, a large specific surface area, a high loading capacity for loading active components, and good stability; wherein the composite use of sodium pyrophosphate and sodium tripolyphosphate can effectively stabilize the catalytic performance while passivating the raw materials to prevent the decomposition of hydroxylamine and methyl octanoate, thereby improving the raw material conversion rate and improving the product yield and purity.

[0019] Preferably, the catalyst is prepared by the following method:

[0020] Lanthanum oxide and tetramethylammonium hydroxide are dissolved in ethanol to obtain an active component impregnation solution, and the catalyst carrier is added with the impregnation solution and ultrasonically dispersed, and then allowed to stand for aging and drying to obtain the product.

[0021] Preferably, the mass ratio of the lanthanum oxide, tetramethylammonium hydroxide and ethanol is 0.1:4:7.

[0022] Preferably, the mass ratio of the catalytic carrier to the impregnation liquid is 1:2.2-2.8.

[0023] By adopting the above-mentioned technical scheme, the present application adopts a compound of lanthanum oxide and tetramethylammonium hydroxide as the active component, and adds ethanol to the active component to prepare an impregnation solution for impregnation of the catalytic carrier. By controlling the mass ratio of the catalytic carrier and the impregnation solution, it is possible to ensure a high loading amount while improving the loading stability. During the reaction, the loaded active components will not fall off and be lost, and the resulting catalyst has strong catalytic activity and good reusability.

[0024] In summary, this application has the following beneficial effects:

[0025] 1. The present invention uses ethanol aqueous solution as solvent medium, hydroxylamine and methyl octanoate as reaction raw materials, catalytic carriers loaded with lanthanum oxide and tetramethylammonium hydroxide as catalysts, optimizes process parameters, and uses green and safe catalysts to catalyze the preparation of octanoylhydroxamic acid. The preparation method of the present invention is simple to operate, has mild reaction conditions, and has a high raw material conversion rate, is suitable for industrial production, and has a high yield of the obtained octanoylhydroxamic acid, high purity, and good product stability.

[0026] 2. The present application uses a composite modification of sodium pyrophosphate and sodium tripolyphosphate when preparing the catalytic carrier. On the one hand, it can significantly improve the problems of poor dispersibility, easy agglomeration and poor catalytic stability of the catalytic carrier. On the other hand, it can also passivate the raw materials and prevent the decomposition of hydroxylamine and methyl octanoate, thereby improving the raw material conversion rate and the product yield and purity.

[0027] 3. The present application adopts a compound of lanthanum oxide and tetramethylammonium hydroxide as the active component, and adds ethanol to the active component to prepare an impregnation solution for impregnation of the catalytic carrier. By controlling the mass ratio of the catalytic carrier and the impregnation solution, it is possible to ensure a high loading amount while improving the loading stability. During the reaction, the loaded active components will not fall off and be lost. The catalyst used in the present application has no strong irritation and toxicity and will not cause pollution to the product. After the reaction is completed, it can be filtered and separated, and the post-processing is simple. The separated catalyst can be reused after a simple activation treatment, and has strong catalytic activity and good reuse performance. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments.

[0029] Preparation Examples 1-10 provide methods for preparing the catalysts.

[0030] Preparation Example 1

[0031] The catalyst was prepared by the following method:

[0032] Sodium pyrophosphate and sodium tripolyphosphate were added to water in a mass ratio of 3:1:10, stirred and dissolved to obtain a mixed solution;

[0033] The mass ratio of the mixed solution, zeolite, silica and silane coupling agent KH550 was controlled to be 10:4:1:0.2, and Dv 50 Zeolite and silica with a particle size of 100 μm were stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, the mixture was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0034] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0035] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid for ultrasonic dispersion for 8 minutes at a mass ratio of 1:2.2. The mixture was then allowed to stand for 4 hours and dried at 120°C to obtain the catalyst.

[0036] Preparation Example 2

[0037] The catalyst was prepared by the following method:

[0038] Sodium pyrophosphate and sodium tripolyphosphate were added to water in a mass ratio of 3:1:10, stirred and dissolved to obtain a mixed solution;

[0039] The mass ratio of the mixed solution, zeolite, silica and silane coupling agent KH550 was controlled to be 10:4:1:0.2, and Dv 50 Zeolite and silica with a particle size of 100 μm were stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, the mixture was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0040] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0041] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid and ultrasonically dispersed for 8 minutes at a mass ratio of 1:2.5. The catalyst was then aged for 4 hours and dried at 120°C to obtain the catalyst.

[0042] Preparation Example 3

[0043] The catalyst was prepared by the following method:

[0044] Sodium pyrophosphate and sodium tripolyphosphate were added to water in a mass ratio of 3:1:10, stirred and dissolved to obtain a mixed solution;

[0045] The mass ratio of the mixed solution, zeolite, silica and silane coupling agent KH550 was controlled to be 10:4:1:0.2, and Dv 50 Zeolite and silica with a particle size of 100 μm were stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, the mixture was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0046] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0047] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid and ultrasonically dispersed for 8 minutes at a mass ratio of 1:2.8, then allowed to stand and age for 4 hours, and then dried at a temperature of 120°C to obtain the catalyst.

[0048] Preparation Example 4

[0049] The catalyst was prepared by the following method:

[0050] Sodium pyrophosphate and sodium tripolyphosphate were added to water in a mass ratio of 1:3:10, stirred and dissolved to obtain a mixed solution;

[0051] The mass ratio of the mixed solution, zeolite, silica and silane coupling agent KH550 was controlled to be 10:4:1:0.2, and Dv 50 Zeolite and silica with a particle size of 100 μm were stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, the mixture was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0052] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0053] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid for ultrasonic dispersion for 8 minutes at a mass ratio of 1:2.2. The mixture was then allowed to stand for 4 hours and dried at 120°C to obtain the catalyst.

[0054] Preparation Example 5

[0055] The catalyst was prepared by the following method:

[0056] Add sodium pyrophosphate to water in a mass ratio of 4:10, stir and dissolve to obtain a mixed solution;

[0057] The mass ratio of the mixed solution, zeolite, silica and silane coupling agent KH550 was controlled to be 10:4:1:0.2, and Dv 50 Zeolite and silica with a particle size of 100 μm were stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, the mixture was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0058] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0059] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid for ultrasonic dispersion for 8 minutes at a mass ratio of 1:2.2. The mixture was then allowed to stand for 4 hours and dried at 120°C to obtain the catalyst.

[0060] Preparation Example 6

[0061] The catalyst was prepared by the following method:

[0062] Add sodium tripolyphosphate to water in a mass ratio of 4:10, stir and dissolve to obtain a mixed solution;

[0063] The mass ratio of the mixed solution, zeolite, silica and silane coupling agent KH550 was controlled to be 10:4:1:0.2, and Dv 50 Zeolite and silica with a particle size of 100 μm were stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, the mixture was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0064] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0065] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid for ultrasonic dispersion for 8 minutes at a mass ratio of 1:2.2. The mixture was then allowed to stand for 4 hours and dried at 120°C to obtain the catalyst.

[0066] Preparation Example 7

[0067] The catalyst was prepared by the following method:

[0068] Sodium pyrophosphate and sodium tripolyphosphate were added to water in a mass ratio of 3:1:10, stirred and dissolved to obtain a mixed solution;

[0069] The mass ratio of the mixed solution, zeolite, silica and silane coupling agent KH550 was controlled to be 10:1:4:0.2, and Dv 50 Zeolite and silica with a particle size of 100 μm were stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, the mixture was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0070] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0071] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid for ultrasonic dispersion for 8 minutes at a mass ratio of 1:2.2. The mixture was then allowed to stand for 4 hours and dried at 120°C to obtain the catalyst.

[0072] Preparation Example 8

[0073] The catalyst was prepared by the following method:

[0074] Sodium pyrophosphate and sodium tripolyphosphate were added to water in a mass ratio of 3:1:10, stirred and dissolved to obtain a mixed solution;

[0075] The mass ratio of the mixed solution, zeolite and silane coupling agent KH550 was controlled to be 10:5:0.2, and Dv 50 Zeolite with a particle size of 100 μm was stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, it was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0076] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0077] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid for ultrasonic dispersion for 8 minutes at a mass ratio of 1:2.2. The mixture was then allowed to stand for 4 hours and dried at 120°C to obtain the catalyst.

[0078] Preparation Example 9

[0079] The catalyst was prepared by the following method:

[0080] Sodium pyrophosphate and sodium tripolyphosphate were added to water in a mass ratio of 3:1:10, stirred and dissolved to obtain a mixed solution;

[0081] The mass ratio of the mixed solution, silicon dioxide and silane coupling agent KH550 was controlled to be 10:5:0.2, and Dv 50 Silica with a particle size of 100 μm was stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, it was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0082] Lanthanum oxide and tetramethylammonium hydroxide were dissolved in ethanol at a mass ratio of 0.1:4:7 to obtain an active component impregnation solution;

[0083] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid for ultrasonic dispersion for 8 minutes at a mass ratio of 1:2.2. The mixture was then allowed to stand for 4 hours and dried at 120°C to obtain the catalyst.

[0084] Preparation Example 10

[0085] The catalyst was prepared by the following method:

[0086] Sodium pyrophosphate and sodium tripolyphosphate were added to water in a mass ratio of 3:1:10, stirred and dissolved to obtain a mixed solution;

[0087] The mass ratio of the mixed solution, zeolite, silica and silane coupling agent KH550 was controlled to be 10:4:1:0.2, and Dv 50 Zeolite and silica with a particle size of 100 μm were stirred and dispersed at a stirring speed of 500 r / min for 10 min, and then silane coupling agent KH550 was added and stirred and dispersed for 30 min. Then, the mixture was dried at 120°C, cooled and ground to obtain Dv 50 Catalytic carrier with a particle size of 20 μm;

[0088] Tetramethylammonium hydroxide and ethanol were dissolved in a mass ratio of 4.1:7 to obtain an active component impregnation solution;

[0089] The ultrasonic power was controlled to be 70W, and the catalytic carrier was added with the impregnation liquid for ultrasonic dispersion for 8 minutes at a mass ratio of 1:2.2. The mixture was then allowed to stand for 4 hours and dried at 120°C to obtain the catalyst.

[0090] Embodiments 1-14 provide a method for preparing antibacterial octanoylhydroxamic acid, which is described below using Embodiment 1 as an example.

[0091] Example 1

[0092] A method for preparing bacteriostatic octanoylhydroxamic acid comprises the following steps:

[0093] To 120 g of 85% ethanol aqueous solution, 0.1 g of the catalyst in Preparation Example 1 was added and stirred and dispersed, then 1 g of hydroxylamine and 4.8 g of methyl octanoate were added, the temperature was raised to 38 ° C, and the reaction was stirred at a speed of 120 r / min for 3 h until the reaction was completed. The pH value was adjusted to 6, the precipitate was filtered and recovered, and the filtrate was evaporated to dryness to recover ethanol to obtain a crude product. The crude product was added to 100 g of deionized water at 0 ° C, stirred to precipitate a white solid, and then filtered, washed with water, and dried to obtain the desired octanoylhydroxamic acid.

[0094] Examples 2-5 are the same as Example 1, except that the preparation process parameters are different, as shown in Table 1.

[0095] Table 1:

[0096] Preparation process parameters Example 1 Example 2 Example 3 Example 4 Example 5 Ethanol aqueous solution dosage 120g 120g 120g 120g 120g Ethanol aqueous solution mass fraction 85% 88% 90% 88% 95% Catalyst dosage 0.1g 0.11g 0.12g 0.1g 0.1g Hydroxylamine 1g 1g 1g 1g 1g Methyl octanoate 4.8g 4.9g 5.0g 5.1g 5.2g Reaction temperature 38℃ 40℃ 42℃ 45℃ 40℃ Stirring speed 120r / min 125r / min 130r / min 135r / min 140r / min Reaction time 3h 4h 5h 3.5h 4.5h pH 6 6.2 6.5 6.2 6.4 Deionized water dosage 100g 100g 100g 100g 100g Deionized water temperature 0℃ 0℃ 0℃ 0℃ 0℃

[0097] Examples 6-14 are the same as Example 4, except that the specific catalysts are different, as shown in Table 2.

[0098] Table 2:

[0099] Example Example 4 Example 6 Example 7 Example 8 Example 9 Catalyst selection Preparation Example 1 Preparation Example 2 Preparation Example 3 Preparation Example 4 Preparation Example 5 Example Example 10 Embodiment 11 Example 12 Example 13 Embodiment 14 Catalyst selection Preparation Example 6 Preparation Example 7 Preparation Example 8 Preparation Example 9 Preparation Example 10

[0100] Caprylhydroxamic acid performance test

[0101] The yield and purity of octanoylhydroxamic acid prepared in Examples 1-14 of the present application were respectively detected, and the results shown in Table 3 below were obtained.

[0102] Yield = (output / feed amount) × 100%, where the feed amount is calculated based on the amount of the smaller reactant input;

[0103] Purity: The purity was detected by GC (gas chromatography); purity = (amount of ethyl n-octanoate / output) x 100%.

[0104] Table 3:

[0105]

[0106]

[0107] From the results shown in Table 3 above, we can see that:

[0108] Specifically, it can be seen from Examples 1-7 that the yield and purity of octanoylhydroxamic acid prepared by the antibacterial octanoylhydroxamic acid preparation method proposed in the present application are high, and the comprehensive performance is the best.

[0109] It can be seen from Examples 4, 6-10 that by selecting sodium pyrophosphate and sodium tripolyphosphate as the composite carrier component for modification, when the mass ratio of sodium pyrophosphate to sodium tripolyphosphate is controlled to be 3:1 while the total amount of sodium pyrophosphate and sodium tripolyphosphate remains unchanged, the obtained catalyst has good dispersibility and catalytic stability, and can also passivate the raw materials to prevent the decomposition of the raw materials, thereby improving the raw material conversion rate, and ultimately significantly improving the yield and purity of the obtained product.

[0110] It can be seen from Examples 4 and 11-13 that by selecting a composite of zeolite and silica as the carrier component, while keeping the total amount of zeolite and silica unchanged and controlling the mass ratio of zeolite to silica to 4:1, the catalyst dispersibility and stability can be further improved, thereby increasing the raw material conversion rate and ultimately improving the yield and purity of the product.

[0111] It can be seen from Examples 4 and 14 that the use of lanthanum oxide and tetramethylammonium hydroxide as active components can significantly increase the loading amount and loading stability of the active components, improve the catalytic activity, and significantly improve the product yield and purity under the same reaction conditions.

[0112] Catalyst performance testing

[0113] The precipitate recovered by filtration in Examples 4, 6-14 of the present application was washed with water, dried at 120°C, and ground for reuse; the yield of octanoylhydroxamic acid after 10 reuses was measured, and the results shown in Table 4 were obtained:

[0114] Table 4:

[0115]

[0116]

[0117] From the results shown in Table 4 above, it can be seen that the catalysts prepared in Preparation Examples 1-3 of the present application have high catalytic activity and good reusability. The yield of octanoylhydroxamic acid prepared by the first catalytic reaction is not less than 97%, and after being reused 10 times, a yield of not less than 95.8% can still be obtained.

[0118] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing bacteriostatic octanoylhydroxamic acid, characterized in that: The method comprises the following preparation steps: After adding a catalyst to an ethanol aqueous solution and stirring to disperse, hydroxylamine and methyl octanoate are added and stirred until the reaction is completed, the pH value is adjusted and the precipitate is recovered by filtration, and the filtrate is evaporated to dryness and then recrystallized to obtain octanoylhydroxamic acid; The catalyst comprises a catalytic carrier and an active component; the active component comprises lanthanum oxide and tetramethylammonium hydroxide; The catalyst carrier is prepared by the following method: Add water to sodium pyrophosphate and sodium tripolyphosphate and stir to dissolve to obtain a mixed solution; Add zeolite and silicon dioxide to the mixed solution, stir and mix, then add silane coupling agent and continue to mix, dry and grind to obtain the desired catalytic carrier; The catalyst was prepared by the following method: Lanthanum oxide and tetramethylammonium hydroxide are dissolved in ethanol to obtain an active component impregnation solution, and the catalyst carrier is added with the impregnation solution and ultrasonically dispersed, and then allowed to stand for aging and drying to obtain the product.

2. The method for preparing the antibacterial octanoylhydroxamic acid according to claim 1, characterized in that: The ethanol aqueous solution is an ethanol aqueous solution with a mass fraction of 85-95%.

3. The method for preparing the antibacterial octanoylhydroxamic acid according to claim 1, characterized in that: The mass ratio of the hydroxylamine to methyl octanoate is 1:4.8-5.

2.

4. The method for preparing the antibacterial octanoylhydroxamic acid according to claim 1, characterized in that: The mass ratio of the catalyst to hydroxylamine is 1-1.2:

10.

5. The method for preparing antibacterial octanoylhydroxamic acid according to claim 1, characterized in that: The mass ratio of the sodium pyrophosphate, sodium tripolyphosphate and water is 3:1:

10.

6. The method for preparing antibacterial octanoylhydroxamic acid according to claim 1, characterized in that: The mass ratio of the mixed solution, zeolite, silicon dioxide and silane coupling agent is 10:4:1:0.

2.

7. The method for preparing antibacterial octanoylhydroxamic acid according to claim 1, characterized in that: The mass ratio of the lanthanum oxide, tetramethylammonium hydroxide and ethanol is 0.1:4:

7.

8. The method for preparing antibacterial octanoylhydroxamic acid according to claim 1, characterized in that: The mass ratio of the catalytic carrier to the impregnation liquid is 1:2.2-2.8.

Citation Information

Patent Citations

  • Preparation technology of caprylhydroxamic acid

    CN110845367A

  • Preparation method of safe and bacteriostatic octanoyl hydroxamic acid

    CN115197097A